PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH DI INDONESIA - Anggi Anggeriani Br Ketaren (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine in depth the influence of service quality on customer satisfaction in the Islamic banking industry in Indonesia through a qualitative approach based on a literature review of the latest scientific literature for the period 2020-2026. The main focus of the study lies in the Islamic SERVQUAL model which consists of five main dimensions, namely tangibles in the form of physical facilities that comply with Islamic principles, reliability which includes the reliability of Islamic contracts, responsiveness or responsiveness of services, assurance as a guarantee of compliance with the DSN-MUI fatwa, and empathy in the form of personal service based on trust and Islamic values, which have consistently been proven to be able to increase the level of customer satisfaction through systematic content analysis of various empirical studies. The results of the study indicate that overall service quality has a positive and significant influence on customer satisfaction, with the dimensions of responsiveness and assurance being the most dominant factors because both directly build customer trust in fundamental Islamic principles such as the prohibition of riba, gharar, and maisir which are the characteristics of Islamic banking. Furthermore, the use of digital technologies such as Islamic mobile banking and halal QRIS significantly contribute to improving customer accessibility and convenience, despite still being hampered by low levels of Islamic financial literacy and limited internet access in rural and remote areas. This study concludes that optimizing service quality is a key strategy to strengthen customer retention and loyalty in the rapidly growing Islamic banking industry, with total assets reaching IDR 831.95 trillion in September 2023 (10.94% YoY growth) and reaching IDR 1,028 trillion in October 2025. The resulting strategic recommendations include intensive human resource training based on Islamic SERVQUAL, innovation of halal digital services based on Islamic contracts, and a massive Islamic financial literacy education program to increase the national competitiveness of the Islamic banking industry in the global market.